Two porous luminescent metal–organic frameworks: quantifiable evaluation of dynamic and static luminescent sensing mechanisms towards Fe3+. Issue 39 (16th September 2015) - Jin, Jun-Cheng; Pang, Ling-Yan; Yang, Guo-Ping; Hou, Lei; Wang, Yao-Yu
Abstract : Two novel porous MOFs have been constructed and highly sensitive sensor to Fe 3+ . The quenching mechanisms are studied and the dynamic and static mechanisms for MOFs are discussed. Abstract : Two novel porous luminescent metal–organic frameworks (MOFs, 1 and2 ) have been constructed using 3, 4-di(3, 5-dicarboxyphenyl)phthalic acid using a hydrothermal method. Both MOFs can work as highly sensitive sensors to Fe 3+ by luminescent quenching. Analyses of the structures indicate a higher quenching efficiency of2 because of the existence of active –COOH groups. Based on this consideration, the quenching mechanisms are studied and the processes are controlled by multiple mechanisms in which dynamic and static mechanisms of MOFs are discussed. Besides, the corresponding dynamic and static quenching constants are calculated, achieving the quantification evaluation of the quenching process. As expected, experimental data show that compound2 possesses an overall quenching efficiency 6.9 times that of compound1 . Additionally, time-dependent intensity measurements, the shifts of the excitation spectrum and the appearance of a new emission peak all give visual proofs of the distinct mechanisms between the two MOFs.